In Silico Study of Fatty Acid Compounds in Pure Eel Oil (Anguilla marmorata (Q.) Gaimard) as a Therapeutic Agent for Liver Cancer - Shara Wardhani; Saipul Maulana; Jamaluddin Jamaluddin (Jurnal Kimia Sains dan Aplikasi, 2026)
Liver cancer is a leading cause of cancer-related deaths globally, due to late diagnosis and limited treatment options. Developing aquatic resources as sources of bioactive compounds with anti-inflammatory and antiproliferative activities may provide a potential strategy for exploring alternative therapeutic candidates for liver cancer. Eels (Anguilla marmorata (Q.) Gaimard) are known to contain fatty acids with anti-inflammatory and antiproliferative activities, potentially with anticancer activity. However, there have been no scientific reports related to specific fatty acid compounds in pure eel oil that have the potential to be liver anticancer agents. This study aims to identify the molecular targets of eel oil fatty acids with the potential to inhibit liver cancer cell growth and to analyze molecular interactions and binding affinities with target proteins. The methods used were an integrated computational approach of network pharmacology and molecular docking, accompanied by ADMET prediction. The results of this study showed that network pharmacology analysis predicted three main target proteins, namely SRC, PIK3CA, and PIK3CB, which play an important role in the pathogenesis of liver cancer. The molecular docking results showed that of the 34 eel compounds, six compounds showed strong binding affinity toward SRC, PIK3CA, and PIK3CB, such as 5,8,11,14,17-cis -Eicosapentaenoic Acid (SRC and PIK3CB), Eicosapentaenoic Acid (SRC), Cis-4,7,10,13,16,19 -Docosahexaenoic Acid (SRC, PIK3CA, and PIK3CB), Gamma-Linolenic Acid (PIK3CA), Arachidonic Acid (PIK3CA), and Cis 8,11,14-Eicosatrienoic Acid (PIK3CB). However, these docking scores were weaker than those of the native ligands (approximately −9 to −10 kcal/mol), suggesting relatively weak ATP-binding site occupancy compared with approved inhibitors. ADMET prediction suggested generally favorable ADME properties, and in silico toxicity predictions indicate low acute toxicity risk. In conclusion, this study identified fatty acid compounds from pure eel oil as multi-target therapeutic candidate compounds that may serve as preliminary multi-target candidate compounds for further experimental validation in liver cancer research.